Training Programs and Employee Performance in Public Institutions: A Case of Mbale District Local Government - Tumwa Cirus (Uganda Christian University, 2024)
The study examined the relationship between training programs and employee performance iin Mbale district Local Government Local Government. The objectives that guided the study were; analyzing the relationship between training content, training materials and training methods and employee performance in Mbale district Local Government Local Government in terms of efficiency and effectiveness. The study used a cross sectional survey research design using both quantitative and qualitative approaches. The target population was 176 respondents and the sampling techniques were: simple random sampling and purposive sampling. The questionnaire, interview and documentary review methods were used to collect data. The data collected was analyzed using Pearson’s co-relation co-efficient techniques. According to the study findings, there was a positive relationship between training content and employee performance, there was a positive relationship between training materials and employee performance and there was a positive relationship between training methods and employee performance. The researcher concluded that training content, training materials and training methods have a positive relationship with employee performance. Recommendations of the study were; training needs, materials and methods should be identified at the confluence of the direction in which the Government intends to move, the changes in technology that are occurring, and the career paths employees could be pursuing. The study therefore proposes further research should be conducted on the relationship between reward management and employee performance as well as the impact of resource allocation to capacity building and employee performance